OA phenotypes, rather than disease stage, drive structural progression – identification of structural progressors from 2 phase III randomized clinical studies with symptomatic knee OA. Issue 4 (April 2015) - Karsdal, M.A.; Bihlet, A.; Byrjalsen, I.; Alexandersen, P.; Ladel, C.; Michaels, M.; Andersen, J.R.; Riis, B.J.; Kraus, V.; Bay-Jensen, A.C.; Christiansen, C.
Summary: Background/Purpose: The aim of this study was to identify key characteristics of disease progression through investigation of the association of radiographic progression over two years with baseline Joint Space Width (JSW), Kellgren–Lawrence (KL) grade, Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain, Joint Space Narrowing (JSN), and BMI. Methods: Data from 2206 subjects (4390 knees) were combined for this post-hoc analysis of two randomized, double-blind, multi-center, placebo-controlled phase III trials (NCT00486434 and NCT00704847 ) that evaluated the efficacy and safety of 2-years treatment with oral salmon calcitonin of subjects with painful knee osteoarthritis (OA). Results: There was a clear positive and significant correlation between KL grade and WOMAC pain and total WOMAC, albeit the variance in pain measures was from min-to-max for all KL categories, emphasizing the heterogeneity of this patient population and pain perception. 32% of target knees did not progress, and only 51% had changes over minimum significant change (MSC). BMI, KL-Score and WOMAC pain was diagnostic, but only KL-score and pain had prognostic value, albeit pain in a non-linear manner. Conclusion: These data clearly describe significant associations between KL grade, JSW, pain and BMI in patients with symptomatic knee OA. KL grade, BMI and WOMAC pain were diagnostically associated with OA based on JSW but only KL-score and pain in a non-linier fashion was prognostic. 50% of patients did not progress more than MSC, highlighting the importance for identification of structural progressors and the phenotypes associated with these. These results suggest that disease phenotypes, rather than disease status, are responsible for disease progression.